PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH UNTUK MENINGKATKAN KETERAMPILAN MEMBACA PEMAHAMAN SISWA DI SEKOLAH DASAR - Sari, Nanda; Nurhaswinda, Nurhaswinda; Pahrul, Yolanda (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
This research was motivated by the low reading comprehension skills of third grade students at SDN 035 Indra Puri, Tapung District, Kampar Regency. One solution to overcome this problem is to use the make a match learning model. The purpose of this study was to determine the planning, implementation and improvement of the make a match learning model in improving reading comprehension skills through third grade students at SDN 035 Indrapuri. This research method is classroom action research (PTK) which is carried out in two cycles. Each cycle consists of two meetings and four stages, namely planning, implementing, observing and reflecting. The results of data analysis showed that the average value from cycle I to cycle II increased by 17.5 from 59.23 to 76.73. This means that there was a significant increase. Similarly, student completeness also increased from 54% to 85%. Thus it can be concluded that the make a match learning model can improve the reading skills of class III students at SDN 035 Inra Puri, especially in the theme of Love the Animals and Plants Around..